Performance comparison of flat static and adjustable angle solar panels for sunny weather - Chua Y.L.; Yong Y.K. (American Institute of Physics Inc., 2023)
Nowadays solar panels are commonly used to collect sunlight so that it could convert solar energy into electrical energy. The power generated by the solar panels depends on the amount of sunlight collected on the solar panels. This paper presents a study that was carried out to study how changing the angle of the solar panels will impact the amount of electrical energy collected after conversion and the efficiencies of the solar panels. In this paper, the solar panels were placed at 30, 35and 40angles throughout different days. The energy collected is then compared with energy collected by a flat static solar panel. It turns out that the solar panels with 40angle performed best among the other angle solar panels. 2017 Author(s).